Transdermal delivery of poly-hyaluronic acid-based spherical nucleic acids for chemogene therapy. Issue 5 (18th January 2022) - Jiang, Kai; Zhao, Di; Ye, Rui; Liu, Xinlong; Gao, Chao; Guo, Yuanyuan; Zhang, Chuan; Zeng, Jian; Wang, Shi; Song, Jie
Abstract : PHAAD NPs, PHA-based spherical nucleic acids, represent a new transdermal delivery system for efficient combinatorial chemo and gene therapy for HS therapy. Abstract : Spherical nucleic acid (SNA), as a good gene delivery system, has a good application prospect for transdermal administration in skin disorder treatment. However, most of the traditional SNA core materials are non-degradable materials, so it is worthy of further research. Herein, we report a spherical nucleic acid based on poly-hyaluronic acid (PHA) for the co-delivery of a typical chemotherapeutic drug, doxorubicin (DOX), and an antisense oligonucleotide (ASO) against the tissue inhibitor of metalloproteinases 1 (TIMP-1) for the treatment of hypertrophic scars (HS) which are caused by abnormal fibroblast proliferation. Our study showed that PHA-based SNAs simultaneously bearing TIMP-1 ASO and DOX (termed PHAAD) could significantly promote skin penetration, improve the cellular uptake, and effectively down-regulate the TIMP-1 expression and enhance the cytotoxicity of DOX. Moreover, PHAAD nanoparticles facilitated the apoptosis of hypertrophic scar cells, and reduced the burden and progression of hypertrophic scars in a xenografted mouse model without adverse side effects. Thus, our PHA-based SNA represents a new transdermal delivery vehicle for efficient combinatorial chemo and gene therapy, which is expected to treat various skin disorders.